A complementary perspective on business ethics in South Korea: Civil religion, common misconceptions, and overlooked social structures. (27th July 2017) - Horak, Sven; Yang, Inju
Abstract : Following the recent call for advancement in knowledge about business ethics in East Asia, this study proposes a complementary perspective on business ethics in South Korea. We challenge the conventional view that South Korea is a strictly collectivist country, where group norms and low trust determine the norms and values of behavior. Using the concept of civil religion, we suggest that the center of the South Korean civil religion can be seen in the affective ties and networks pervading the economic, political, and social institutions, embedded in and guided by Confucian ideals. We argue that South Korea should be seen not as a collectivist low‐trust society, but rather as an affective‐relational society, in which the relational context determines whether collectivism or individualism prevails. Further, we assert that trust, the cohesive factor of affective ties and networks, has until now been inadequately captured by conventional surveys. Our proposed perspective contributes to a more holistic picture and a more firmly grounded understanding of business ethics in South Korea.